Electrical Characteristics And Thermal Stability Of Ti Contact To p-Gan. - Tan, C.K.; Abdul Aziz, A.; Hassan, Z.; Tam, F.K.; Hudeish, A.Y. (2005)
Wide band gap GaN semiconductor has a variety of applications in optoelectronic devices such as lightemitting diodes and laser diodes.